Seasonal dependence of northern high‐latitude upper thermospheric winds: A quiet time climatological study based on ground‐based and space‐based measurements. Issue 2 (28th February 2017) - Dhadly, Manbharat; Emmert, John; Drob, Douglas; Conde, Mark; Doornbos, Eelco; Shepherd, Gordon; Makela, Jonathan; Wu, Qian; Niciejewski, Rick; Ridley, Aaron
Abstract: This paper investigates the large‐scale seasonal dependence of geomagnetically quiet time, northern high‐latitude F region thermospheric winds by combining extensive observations from eight ground‐based (optical remote sensing) and three space‐based (optical remote sensing and in situ) instruments. To provide a comprehensive picture of the wind morphology, data are assimilated into a seasonal empirical vector wind model as a function of season, latitude, and local time in magnetic coordinates. The model accurately represents the behavior of the constituent data sets. There is good general agreement among the various data sets, but there are some major offsets between GOCE and the other data sets, especially on the duskside. The assimilated wind patterns exhibit a strong and large duskside anticyclonic circulation cell, sharp latitudinal gradients in the duskside auroral zone, strong antisunward winds in the polar cap, and a weaker tendency toward a dawnside cyclonic circulation cell. The high‐latitude wind system shows a progressive intensification of wind patterns from winter to equinox to summer. The latitudinal extent of the duskside circulation cell does not depend strongly on season. Zonal winds show a mainly diurnal variation (two extrema) around polar and middle latitudes and semidiurnal variation (four extrema) at auroral latitudes; meridional winds are primarily diurnal at all high latitudes. The strength of zonal winds channeling through the auroral zone on the duskside is strongest in the summer season. The vorticity of the wind pattern increases from winter to summer, whereas divergence is maximum in equinox. In all three seasons, divergence is weaker than vorticity. Key Points: First ever investigation of the large‐scale seasonal dependence of northern high‐latitude upper thermospheric winds in magnetic coordinates Results show progressive intensification of wind circulation from winter to equinox to summer The vorticity increases from winter to summer. In all the seasons, the strongest divergences occur primarily in and above auroral latitudes